Nutritional status and related factors in schoolchildren (Research, Society and Development, 2020)
The study aimed to verify the nutritional status of students of the final years of elementary school from a public school on the western border of Rio Grande do Sul. The sample consisted of 222 students from 6th to 9th grade of elementary school. Nutritional status was assessed based on the relationship between body mass index (BMI) and age and gender of the student, using the International Physical Activity Questionnaire - IPAQ Short Version. To analyze eating habits and nutrition knowledge, a questionnaire based on pre-existing questionnaires was applied. It was observed that 56.7% of students had normal weight in relation to height, age and gender (eutrophy), however, were found high rates of overweight and obesity, which together reach 42.8% of the sample. Regarding eating habits, most students were classified as “regular eating habits” (77.6%), followed by “bad eating habits” (18%) and “good eating habits” (4.4%). Regarding nutritional knowledge, it was found that 85.3% were classified with low nutritional knowledge, 14.7% with moderate nutritional knowledge and none with high nutritional knowledge. Regarding the level of habitual physical activity, most are classified as “Active” (66.5%) or “Very Active” (28.1%), while 4.3% were classified as “Irregularly Active A”. and 1.1% as “Irregularly Active B”. In general, students have a higher body mass index than expected for their height and age (overweight / obese), with regular eating habits, with a large deficit in terms of nutritional knowledge and are physically active.